Definitely integrable

Calculus Level 4

0 2 ln ( 1 + 2 x ) 1 + x 2 d x = arctan a ln b \int_0^2 \frac{\ln (1+2x)}{1+x^{2}} dx = \arctan a \cdot \ln\sqrt b

The equation above holds true for natural numbers a a and b b . Find a 4 + b 4 a^4+b^4 .

Inspiration: IIT-JEE


The answer is 641.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Guilherme Niedu
Sep 27, 2019

An alternative solution to Mr @Hrithik Thakur:

I = 0 2 ln ( 1 + 2 x ) 1 + x 2 d x \large \displaystyle I = \int_0^2 \frac{\ln (1 + 2x)}{1+x^2} dx

Let x = tan ( θ ) x = \tan (\theta) . Also d x = sec 2 ( θ ) d θ d θ = d x 1 + x 2 dx = \sec^2 (\theta) d \theta \rightarrow d \theta = \frac{dx}{1+x^2} and the limits of integration will be 0 0 and arctan ( 2 ) \arctan (2) . Let us call ϕ = arctan ( 2 ) \phi = \arctan (2) :

I = 0 ϕ ln ( 1 + 2 tan ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln (1 + 2 \tan(\theta) ) d \theta

I = 0 ϕ ln ( cos ( θ ) + 2 sin ( θ ) ) cos ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln \left ( \frac{\cos (\theta) + 2 \sin(\theta) )}{\cos(\theta)} \right ) d \theta

I = 0 ϕ ln ( cos ( θ ) + 2 sin ( θ ) ) d θ 0 ϕ ln ( cos ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln (\cos (\theta) + 2 \sin(\theta)) d \theta - \int_0^{\phi} \ln (\cos (\theta)) d \theta

Inside the ln \ln of the first integral, we can multiply above and below by 5 \sqrt{5} :

I = 0 ϕ ln [ 5 ( cos ( θ ) 5 + 2 sin ( θ ) 5 ) ] d θ 0 ϕ ln ( cos ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln \left [ \sqrt{5} \left ( \frac{\cos (\theta)}{\sqrt{5}} + 2 \frac{\sin(\theta)}{\sqrt{5}} \right ) \right ] d \theta - \int_0^{\phi} \ln (\cos (\theta)) d \theta

Notice that if ϕ = arctan ( 2 ) \phi = \arctan (2) , cos ( ϕ ) = 1 5 \cos(\phi) = \frac{1}{\sqrt{5}} and sin ( ϕ ) = 2 5 \sin(\phi) = \frac{2}{\sqrt{5}} :

I = 0 ϕ ln [ 5 ( cos ( θ ) cos ( ϕ ) + sin ( θ ) sin ( ϕ ) ) ] d θ 0 ϕ ln ( cos ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln \left [ \sqrt{5} \left (\cos (\theta) \cos(\phi) + \sin(\theta)\sin(\phi) \right ) \right ] d \theta - \int_0^{\phi} \ln (\cos (\theta)) d \theta

I = 0 ϕ ln ( 5 ) d θ + 0 ϕ ln ( cos ( θ ϕ ) ) d θ 0 ϕ ln ( cos ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln(\sqrt{5})d \theta + \int_0^{\phi} \ln(\cos(\theta - \phi))d \theta - \int_0^{\phi} \ln (\cos (\theta)) d \theta

In the second integral make u = ϕ θ u = \phi - \theta . Then d u = d θ du = - d \theta :

I = 0 ϕ ln ( 5 ) d θ + ϕ 0 ln ( cos ( u ) ) d u 0 ϕ ln ( cos ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln(\sqrt{5})d \theta + \int_{\phi} ^0- \ln(\cos(-u))du - \int_0^{\phi} \ln (\cos (\theta)) d \theta

Since cosine is even:

I = 0 ϕ ln ( 5 ) d θ + 0 ϕ ln ( cos ( u ) ) d u 0 ϕ ln ( cos ( θ ) ) d θ \large \displaystyle I = \int_0^{\phi} \ln(\sqrt{5})d \theta + \int_0^{\phi} \ln(\cos(u))du - \int_0^{\phi} \ln (\cos (\theta)) d \theta

The second and the third integral cancel out and:

I = 0 ϕ ln ( 5 ) d θ \large \displaystyle I = \int_0^{\phi} \ln(\sqrt{5})d \theta

I = ln ( 5 ) arctan ( 2 ) \color{#20A900} \boxed{ \large \displaystyle I = \ln(\sqrt{5}) \arctan(2) }

Thus:

a = 2 , b = 5 , a 4 + b 4 = 641 \color{#3D99F6} \large \displaystyle a = 2, b = 5, \boxed{ \large \displaystyle a^4 + b^4 = 641}

Chew-Seong Cheong
Sep 28, 2019

Elaboration on @Hrithik Thakur's solution.

I ( p ) = 0 2 ln ( 1 + p x ) 1 + x 2 d x I ( p ) p = 0 2 x ( 1 + p x ) ( 1 + x 2 ) d x = 1 p 2 + 1 0 2 ( x + p x 2 + 1 p p x + 1 ) d x = 1 p 2 + 1 [ ln ( x 2 + 1 ) 2 + p tan 1 x ln ( p x + 1 ) ] 0 2 = ln 5 + p tan 1 2 ln ( 2 p + 1 ) p 2 + 1 I ( p ) = ln 5 + p tan 1 2 ln ( 2 p + 1 ) p 2 + 1 d p = ln 5 tan 1 p + ln p 2 + 1 tan 1 2 ln ( 2 p + 1 ) p 2 + 1 d p + C where C is the constant of integration. = ln 5 tan 1 p + ln p 2 + 1 tan 1 2 ln ( 2 p + 1 ) p 2 + 1 d p Since I ( 0 ) = 0 C = 0 I ( 2 ) = ln 5 tan 1 2 + ln 5 tan 1 2 I ( 2 ) = tan 1 2 ln 5 \begin{aligned} I(p) & = \int_0^2 \frac {\ln (1+px)}{1+x^2} dx \\ \frac {\partial I(p)}{\partial p} & = \int_0^2 \frac x{(1+px)(1+x^2)} dx \\ & = \frac 1{p^2+1}\int_0^2 \left(\frac {x+p}{x^2+1} - \frac p{px+1} \right) dx \\ & = \frac 1{p^2+1} \left[\frac {\ln (x^2+1)}2 + p\tan^{-1} x - \ln (px+1) \right]_0^2 \\ & = \frac {\ln \sqrt 5 + p\tan^{-1}2 - \ln (2p+1)}{p^2+1} \\ \implies I(p) & = \int \frac {\ln \sqrt 5 + p\tan^{-1}2 - \ln (2p+1)}{p^2+1} dp \\ & = \ln \sqrt 5 \tan^{-1} p + \ln \sqrt{p^2+1} \tan^{-1}2 - \int \frac {\ln (2p+1)}{p^2+1} dp + C & \small \color{#3D99F6} \text{where }C \text{ is the constant of integration.} \\ & = \ln \sqrt 5 \tan^{-1} p + \ln \sqrt{p^2+1} \tan^{-1}2 - \int \frac {\ln (2p+1)}{p^2+1} dp & \small \color{#3D99F6} \text{Since } I(0) = 0 \implies C = 0 \\ I(2) & = \ln \sqrt 5 \tan^{-1} 2 + \ln \sqrt 5 \tan^{-1}2 - I(2) \\ & = \tan^{-1} 2 \ln \sqrt 5 \end{aligned}

Therefore a 4 + b 4 = 2 4 + 5 4 = 641 a^4 + b^4 = 2^4+5^4 = \boxed{641} .

Hrithik Thakur
Sep 26, 2019

Hint: generalize the given integrand as 0 2 ln ( 1 + p x ) 1 + x 2 d x \int_{0}^{2} \frac{\ln(1+px)}{1+x^{2}}dx then use differentiation under integration.

You are missing the d x dx for the integral also use a backslash for all functions in LaTex \ln ln \ln . Function should not be in italic. Need not put text in LaTex. It is difficult and not a standard in Brilliant.org.

Chew-Seong Cheong - 1 year, 8 months ago

Log in to reply

Sir, thanks a lot, for your valuable advice... I would keep those points in mind from now onwards.

Hrithik Thakur - 1 year, 8 months ago

Here's a more general form :-

0 p l n ( 1 + p x ) 1 + x 2 d x = I \int_{0}^{p} \frac{ln(1+px)}{1+x^{2}} dx = I

Let x = t a n ( t ) x=tan(t)

so the integral transforms to:-

0 a r c t a n ( p ) l n ( 1 + p t a n ( t ) ) d t = 0 a r c t a n ( p ) l n ( 1 + p t a n ( a r c t a n ( p ) t ) ) d t \int_{0}^{arctan(p)}ln(1+ptan(t))dt = \int_{0}^{arctan(p)}ln(1+ptan(arctan(p) - t))dt

= 0 a r c t a n ( p ) l n ( 1 + p ( p t a n ( t ) ) 1 + p t a n ( t ) ) d t = \int_{0}^{arctan(p)}{ln(1+p\frac{(p-tan(t))}{1+ptan(t)})}dt

= 0 a r c t a n ( p ) l n ( 1 + p 2 1 + p t a n ( t ) ) d t = \int_{0}^{arctan(p)}{ln(\frac{1+p^{2}}{1+ptan(t)})}dt

So 2 I = 0 a r c t a n ( p ) l n ( 1 + p 2 ) d t 2I = \int_{0}^{arctan(p)}ln(1+p^{2}) dt

2 I = a r c t a n ( p ) l n ( 1 + p 2 ) 2I = arctan(p)ln(1+p^{2})

I = a r c t a n ( p ) l n ( 1 + p 2 ) I = arctan(p)ln(\sqrt{1+p^{2}})

Plug in p = 2 p=2 to get the answer .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...